1, 1, 1‐Trichlorethan [MAK Value Documentation in German language, 2019]. Issue 2 (25th April 2019) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the maximum concentration at the workplace (MAK value) and the Pregnancy Risk Group of 1, 1, 1‐trichloroethane [71‐55‐6 ]. Critical are pre‐narcotic effects observed in male volunteers exposed at rest to 350 ml/m 3 . The MAK value has now been lowered to 100 ml/m 3 taking into account the increased respiratory volume at the workplace because the blood:air partition coefficient of 1, 1, 1‐trichlorethane is > 5 (see List of MAK and BAT Values, Section I b and I c). As a systemic effect is critical, Peak Limitation Category II is retained. To avoid short‐term pre‐narcotic effects, the excursion factor of 1 is also retained. The differences between the MAK value and the NOAECs for developmental toxicity in rats, rabbits and mice are sufficient even taking into account the increased respiratory volume at the workplace. Therefore, damage to the embryo or foetus is unlikely when the MAK value is not exceeded and 1, 1, 1‐trichloroethane remains assigned to Pregnancy Risk Group C. 1, 1, 1‐Trichloroethane is neither carcinogenic in rats or mice nor a germ cell mutagen. The designation with "H" (for substances that can be absorbed via the skin in toxicologically relevant amounts) is retained. There are no data on the sensitizing potential in humans. 1, 1, 1‐Trichloroethane is not a skin sensitizer in guinea pigs.